Los salvajes en el cine : notas sobre un mito en movimiento - Bartra, Roger, 1942- (Tezontle., 2018)
In The savages in cinema, Roger Bartra shows us how the mythical savages keep invading the western civilization and have gotten used to the new scientific and technological landscapes. The guiding thread of this work is the mythical condition of these characters that have existed in the Western imagination for millenniums and that in the cinema they acquired certain particular characteristics, here we see vampires, werewolves, mummies, cyborgs, robots, superheroes and others.